Cloud-assisted mutual authentication and privacy preservation protocol for telecare medical information systems. (April 2018) - Li, Chun-Ta; Shih, Dong-Her; Wang, Chun-Cheng
Highlights: We develop an efficient and secure authentication protocol with privacy preservation for cloud-assisted telecare medical information systems. Our enhanced protocol can not only repair the security problems of Mohit et al.'s authentication protocol, but also provide extra functionality features than prior studies. We performed an experiment on the execution time between our enhanced protocol with existing cloud-assisted authentication protocols for medical care systems. It shows that our protocol has lower computational cost and higher security than other related protocols. Abstract: Background and Objective:  With the rapid development of wireless communication technologies and the growing prevalence of smart devices, telecare medical information system (TMIS) allows patients to receive medical treatments from the doctors via Internet technology without visiting hospitals in person. By adopting mobile device, cloud-assisted platform and wireless body area network, the patients can collect their physiological conditions and upload them to medical cloud via their mobile devices, enabling caregivers or doctors to provide patients with appropriate treatments at anytime and anywhere. In order to protect the medical privacy of the patient and guarantee reliability of the system, before accessing the TMIS, all system participants must be authenticated. Methods:  Mohit et al. recently suggested a lightweight authentication protocol for cloud-based health care system. They claimed their protocol ensures resilience of all well-known security attacks and has several important features such as mutual authentication and patient anonymity. In this paper, we demonstrate that Mohit et al.'s authentication protocol has various security flaws and we further introduce an enhanced version of their protocol for cloud-assisted TMIS, which can ensure patient anonymity and patient unlinkability and prevent the security threats of report revelation and report forgery attacks. Results:  The security analysis proves that our enhanced protocol is secure against various known attacks as well as found in Mohit et al.'s protocol. Compared with existing related protocols, our enhanced protocol keeps the merits of all desirable security requirements and also maintains the efficiency in terms of computation costs for cloud-assisted TMIS. Conclusions:  We propose a more secure mutual authentication and privacy preservation protocol for cloud-assisted TMIS, which fixes the mentioned security weaknesses found in Mohit et al.'s protocol. According to our analysis, our authentication protocol satisfies most functionality features for privacy preservation and effectively cope with cloud-assisted TMIS with better efficiency.